Attachment and Intrasexual Competitiveness in Committed Individuals from Chile - Fernandez-Tapia, A (PsychOpen, 2019)
The present research examined the association between intrasexual competitiveness (as an adaptive feature of human mating) and adult attachment dimensions (which develop throughout ontogeny and are relatively stable patterns of relationship approaching in adulthood), postulating that the dimensions of attachment will be predictive of intrasexual competitiveness (the negative perception of same sex-others as potential mating rivals), but in particular attachment anxiety should be correlated to intrasexual competitiveness. We assessed intrasexual competitiveness and the attachment dimensions (closeness, dependence, anxiety, and avoidance) in a sample of 323 adult heterosexual men and women which were currently involved in a romantic relationship and were married or in a cohabiting living arrangement. The results show the expected prediction of intrasexual competitiveness by attachment anxiety, but not by any other adult attachment dimension, suggesting that individuals who develop attachment anxiety are characterized by increased same-sex rivalry and competitiveness, which may negatively affect their same-sex close relationships, in addition to other interpersonal realms. © 2019, PsychOpen. All rights reserved.
Keywords: Human mating; Interpersonal relationships; Same-sex rivalry; Working models of attachment